2001
DOI: 10.1121/1.1367243
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in detecting a mistuned harmonic

Abstract: The effects of age on discriminating simultaneous sounds were investigated by comparing the hearing threshold in detecting a mistuned harmonic in young, middle-aged, and older adults. The stimuli were complex sounds containing multiple harmonics, one of which could be "mistuned" so that it was no longer an integer multiple of the fundamental. Older adults had higher thresholds than middle-aged or young adults. The effect of age was greater for short than for long duration sounds and remained even after control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“…They reported that the amplitude of component Pa of the MLAER increased with mistuning. Significant changes in Pa amplitude occurred at latencies as short as 32 msec, extending the authors' previous studies in which mistuning had produced changes in evoked and eventrelated potentials with longer latencies (Alain et al, 2001(Alain et al, , 2002. Perceptual segregation of the mistuned component was measured in a separate series of trials, from a subset of the listeners who provided the evoked-potential data.…”
Section: Evoked Potentials In Response To Mistuned Tonessupporting
confidence: 70%
“…They reported that the amplitude of component Pa of the MLAER increased with mistuning. Significant changes in Pa amplitude occurred at latencies as short as 32 msec, extending the authors' previous studies in which mistuning had produced changes in evoked and eventrelated potentials with longer latencies (Alain et al, 2001(Alain et al, , 2002. Perceptual segregation of the mistuned component was measured in a separate series of trials, from a subset of the listeners who provided the evoked-potential data.…”
Section: Evoked Potentials In Response To Mistuned Tonessupporting
confidence: 70%
“…This amount of mistuning is considerably large and was chosen because it usually leads to a "pop-out" effect, in much the same way that a visual target defined by a unique color pops out of a display filled with homogeneous distractors defined by a secondary color (Treisman and Gelade, 1980). This amount of mistuning is also well above older adults' thresholds for detecting mistuning, which averaged ϳ5-6% for 100 ms sounds (Alain et al, 2001a). More importantly, the effect of age on concurrent sound perception remains even after controlling for differences in hearing sensitivity between young and older adults.…”
Section: Discussionmentioning
confidence: 93%
“…This small discrepancy between our findings and those of Hiraumi et al (2005) may be related to several factors, including differences in sound duration, number of trials presented to participants, and the utilization of fixed versus random sound presentation. For example, previous behavioral research has shown that detecting harmonicity decreased with increasing sound duration (Moore et al, 1985;Alain et al, 2001a). Hence, it is possible that the longer stimulus durations used by Hiraumi et al (2005) have generated earlier ORN latencies, which would have overlapped the N1 wave and caused an enhanced N1 amplitude and shift in latency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the processing of those primitive grouping cues represents processing by additional peripheral, central, and cognitive mechanisms, as suggested by the involvement of a multi-stage processing model Alain et al, 2005;Alain, 2005, 2007). Especially, Alain et al (2001) showed that age-related deficits in detecting a mistuned harmonic depended not only on the listeners' peripheral factors but also upon an age-related decline in central auditory functioning. As noted, however, on a group basis there were no significant differences in call-sign detection among the four groups.…”
Section: Discussionmentioning
confidence: 99%